2012
DOI: 10.2174/1745017901208010169
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Urban / Rural Living: Preliminary Results of a Community Survey in Italy

Abstract: Background:The purpose of this population-based study is to examine the association between subjective quality of life and rural/urban residence in six Italian regions, including age and gender into the analysis.Methods:Study design:community survey.Study population:Samples stratified according to sex and age, drawn from municipal records. Sample size: 4999 people 18 years and older, from seven communities within six regions of Italy.Tools:Ad-hoc form to assess basic demographic data; SF-12. Interviewers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Ten studies focused on quality of life, well-being and related concepts such as life satisfaction or successful aging [ 33 , 54 , 62 , 63 , 96 - 101 ] (Table 3 ). Among these studies, several distinct environment variables were used, so that a broad analysis was not possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies focused on quality of life, well-being and related concepts such as life satisfaction or successful aging [ 33 , 54 , 62 , 63 , 96 - 101 ] (Table 3 ). Among these studies, several distinct environment variables were used, so that a broad analysis was not possible.…”
Section: Resultsmentioning
confidence: 99%
“…It was considered that some of the studies had insufficient group or subgroup size to make strong statistical inferences [ 52 , 54 , 62 , 100 ]. Some studies had a considerable loss of enrolled participants, a high number of people who refused to participate or participation bias, all of which can lead to misinterpretation of the results [ 36 , 78 , 101 ]. It has been suggested that in some studies, cases were more predisposed than controls to report problems.…”
Section: Resultsmentioning
confidence: 99%
“…The first refers to a sample of citizens of Bogotá (Colombia) aged 60 or more, in which perceived features of built environment, namely street noise, safety of public areas and street crossings were found to be significantly associated with QoL [ 65 ]. In a second study from Italy, the features of built environment were restricted to living in an urban or rural context only, and significant group differences were found only among male respondents [ 66 ]. Such a way to address features of built environment is largely partial, as it provides no indication on the degree to which the context in which the persons live has any facilitating or hindering effect.…”
Section: Discussionmentioning
confidence: 99%
“…QOL refers to individuals’ perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns. The QOL in the four domains can be affected by different factors like age, sex, rural and urban areas [ 2 , 3 ], and health and disease status [ 4 ].…”
Section: Introductionmentioning
confidence: 99%